Plasmid Dynamics of mcr-1-Positive Salmonella spp. in a General Hospital in China - Fan, Jianzhong; Zhang, Linghong; He, Jintao; Zhao, Maoying; Loh, Belinda; Leptihn, Sebastian; Yu, Yunsong; Hua, Xiaoting (Frontiers in Microbiology, 2020)
Salmonella is an important food pathogen that can cause severe gastroenteritis with more than 600,000 deaths globally every year. Colistin, a last-resort antibiotic, is ineffective in bacteria that carry a functional mcr-1 gene, which is often spread by conjugative plasmids. Our work aimed to understand the prevalence of the mcr-1 gene in clinical isolates of Salmonella, as the frequency of occurrence of the mcr-1 gene is increasing globally. Therefore, we analyzed 689 clinical strains, that were isolated between 2009 and late 2018. The mcr-1 gene was found in six strains, which we analyzed in detail by whole genome sequencing and antibiotic susceptibility testing, while we also provide the clinical information on the patients suffering from an infection. The genomic analysis revealed that five strains had plasmid-encoded mcr-1 gene located in four IncHI2 plasmids and one IncI2 plasmid, while one strain had the chromosomal mcr-1 gene originated from plasmid. Surprisingly, in two strains the mcr-1 genes were inactive due to disruption by insertion sequences (ISs): ISApl1 and ISVsa5. A detailed analysis of the plasmids revealed a multitude of ISs, most commonly IS26. The IS contained genes that meditate the broad resistance towards most antibiotics underlining their importance of the mobile elements, also with respect to the spread of the mcr-1 gene. Our study demonstrated the potential reservoirs for transmission of colistin resistance and offered insights to the evolution of mcr-1 gene in Salmonella.